SCHOOLS OF HIGHER EDUCATION VERSUS LOCAL LABOUR MARKET. THE CASE OF SCHOOL BIAŁAPODLASKA - Adamowicz, Mieczysław; Pyra, Mariusz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The State Professional Schools of Higher Education constitute an important sector of higher education in Poland. They are the results of the transformation process of the last decade of the 20th century. Since 1999, 36 public professional schools have been organized. After consolidation, there are 33 state professional schools which concentrate on educational activity, however some at them conduct research and other academic activity. The main aim of the paper is an evaluation of the functioning of this type of schools in the context of local labour market on the case of Pope John Paul II State School of Higher Education in Biała Podlaska, which for several years has been the leading organization in higher education sector in Poland. Sources of materials for research were found in literature, official documents of the school and own diagnostic survey with the use of questionnaires directed to 15 teachers, 105 students and 21 business representatives, which were subsequently analysed. Research results proved that there are some discrepancies between demand and supply on the local labour market in the group of higher education sector. Comparing to the educational fields offered by the State School of Higher Education in Biała Podlaska, there is a shortage of workers in such professions as: IT specialists, physiotherapists, construction engineers while the excess of supply exists for foreign language teachers, sociologists, economists, tourism servants, agricultural engineers. In conclusion, a stronger links between professional schools, enterprises and local organisations are suggested. Implementation of practical profile of students requires some changes in curricula as well as in the system of cooperation between schools and regional labour markets.